Receptor-Mediated Delivery of Astaxanthin-Loaded Nanoparticles to Neurons: An Enhanced Potential for Subarachnoid Hemorrhage Treatment - You, Zong-qi; Wu, Qi; Zhou, Xiao-ming; Zhang, Xiang-sheng; Yuan, Bin; Wen, Li-li; Xu, Wei-dong; Cui, Sheng; Tang, Xiang-long; Zhang, Xin (Frontiers in Neuroscience, 2019)
Astaxanthin (ATX) is a carotenoid that exerts strong anti-oxidant and anti-inflammatory property deriving from its highly unsaturated molecular structures. However, the low stability and solubility of ATX results in poor bioavailability, which markedly hampers its application as therapeutic agent in clinic advancement. This study investigated a promising way of transferrin conjugated to poly (ethylene glycol) (PEG)-encapsulated ATX nanoparticles (ATX-NPs) on targeted delivery and evaluated the possible mechanism underlying neuroprotection capability. As a result, the ATX integrated into nanocarrier presented both well water-dispersible and biocompatible, primely conquering its limitations. More than that, the transferrin-containing ATX-NPs exhibited enhanced cellular uptake efficiency than that of ATX-NPs without transferrin conjugated in primary cortical neurons. Additionally, compared to free ATX, transferrin-containing ATX-NPs with lower ATX concentration showed powerful neuroprotective effects on OxyHb-induced neuronal damage. Taken together, the improved bioavailability and enhanced neuroprotective effects enabled ATX-NPs as favorable candidates for targeted delivery and absorption of ATX. We believe that these in vitro findings will provide insights for advancement of subarachnoid hemorrhage (SAH) therapy.